The effect of (a)synchronous music on runners' lower leg impact loading. (September 2019) - Lorenzoni, Valerio; De Bie, Tijl; Marchant, Thierry; Van Dyck, Edith; Leman, Marc
Running with musical accompaniment is becoming increasingly popular and several pieces of software have been developed that match the music tempo to the exerciser's running cadence, that is, foot strikes per minute. Synchronizing music with running cadence has been shown to affect several aspects of performance output and perception. The purpose of this study was to investigate the effect of synchronous music on runners' foot impact loading. This represents the ground reaction force on the runner's lower leg when the foot impacts the ground and is an important parameter for the prevention of tibial fracture injuries. Twenty-eight participants ran five times for three minutes and 30 seconds with a short break between each run. During the first 30 seconds of each running sequence, participants ran at a self-paced tempo without musical accompaniment, and running speed and cadence were measured. Subsequently, they were requested to keep their reference speed constant for the following three minutes, with the help of three monitoring screens placed along the track. During this part of the experiment, the music was either absent ( No Music ), matched to the runner's cadence ( Tempo-entrained Sync ), phase-locked with foot strikes ( Phase-locked Sync ), or played at a tempo 30% slower ( Minus 30%) or faster ( Plus 30%) than the initially measured running cadence. No significant differences between synchronous and asynchronous music were retrieved for impact loading. However, a non-negligible average increase of impact level could be observed for running sessions with music compared to running in silence. These findings might be especially relevant for treatment purposes, such as exercise prescription and gait retraining, and should be taken into account when designing musical (re-)training programmes.